Interfacial Microenvironment Modulation Enhancing Catalytic Kinetics of Binary Metal Sulfides Heterostructures for Advanced Water Splitting Electrocatalysts. Issue 1 (4th December 2021) - Qian, Yongteng; Yu, Jianmin; Zhang, Ya; Zhang, Fangfang; Kang, Yingbo; Su, Chenliang; Shi, Hu; Kang, Dae Joon; Pang, Huan
Abstract: Interfacial microenvironment modulation has been proven to be a promising route to fabricate highly efficient catalysts. In this work, the lattice defect‐rich NiS2 /MoS2 nanoflakes (NMS NFs) electrocatalysts are successfully synthesized by a simple strategy. Benefiting from the abundant lattice defects and modulated interfacial microenvironment between NiS2 and MoS2, the prepared NMS NFs show superior catalytic activity for water splitting. Particularly, the optimized NMS NFs (the molar ratio of Ni:Mo = 5:5) exhibit remarkable catalytic activity toward overall water splitting with a voltage of 1.60 V at 10 mA cm −2 in alkaline media, which is lower than that of the noble‐metal‐based electrocatalysts (1.68 V at 10 mA cm −2 ). The NMS NFs electrocatalysts also show exceptional long‐term stability (>50 h) for overall water splitting. The density functional theory results demonstrate that the injection of NiS2 into MoS2 can greatly optimize the catalytic kinetics and reduce the energy barrier for hydrogen/oxygen evolution reactions. The work does not only offer a promising candidate for a highly efficient water splitting electrocatalyst but also highlights that interfacial microenvironment modulation is a potential strategy to optimize the catalytic kinetics. Abstract : The defect‐rich NiS2 /MoS2 nanoflakes (NMS NFs) have been successfully synthesized by a simple method. The NMS NFs present remarkable electrocatalytic performances, including the small overpotentials for the oxygen evolution reaction (270 mV at 10 mA cm −2 ) and hydrogen evolution reaction (90 mV at 10 mA cm −2 ), as well as a low voltage for overall water splitting (1.60 V at 10 mA cm −2 ).